La tutela della sicurezza sul lavoro nelle attività all’aperto con l’uso dei droni (SAPR) - Pascucci, Paolo (Cultura giuridica e diritto vivente, 2020)
[Health and safety at work in outdoor activities, with particular reference to the use of SAPR] The article analyzes the problems related to the protection of health and safety at work in outdoor activities with the use of SAPR (aeronautical system with remote pilot). In particular, the analysis focuses on the relevanceof the risks for people unrelated to the organization that uses SAPR and on the need for arisk assessment that also considers these risks.